War and international justice : a Kantian perspective - Orend, Brian, 1971- (Wilfrid Laurier University Press, 2000)
"Brian Orend explores the ethics of war and peace from a Kantian perspective, emphasizing human rights protection, the rule of international law and a fully global concept of justice. Contending that Kant's just war doctrine has not been given its due, Orend displays Kant's theory to its fullest, impressive effect. He then completely and clearly updates Kant's perspective for application to our time."--Jacket.